Risk of neuroinflammatory events in arthritis patients treated with tumour necrosis factor alpha inhibitors: a collaborative population-based cohort study from Denmark and Sweden. Issue 5 (11th March 2020) - Kopp, Tine Iskov; Delcoigne, Bénédicte; Arkema, Elizabeth V; Jacobsen, Rikke Kart; Magyari, Melinda; Ibfelt, Else Helene; Locht, Henning; Sellebjerg, Finn; Cordtz, Rene Lindholm; Jensen, Dorte V; Askling, Johan; Dreyer, Lene
Abstract : Objectives: To investigate whether tumour necrosis factor alpha inhibitors (TNFis) are associated with an increased risk of neuroinflammatory diseases among patients with arthritic diseases. Methods: Cohorts of patients with rheumatoid arthritis (RA, n=25 796), psoriatic arthritis (PsA, n=8586) and ankylosing spondylitis (AS, n=9527) who initiated a TNFi treatment year 2000–2017 were identified from nationwide clinical rheumatology registers in Sweden and Denmark. Information on demyelinating disease and inflammatory neuropathy diagnoses was retrieved from prospective linkage to National Patients Register. A Cox proportional hazard model was used to estimate HRs and 95% CI comparing TNFi exposed and non-exposed, by disease and country. Results: Among 111 455 patients with RA, we identified 270 (Sweden) and 51 (Denmark) events (all types of neuroinflammatory diseases combined), corresponding to crude incidence rates (per 1000 person-years) of 0.37 (Sweden) and 0.39 (Denmark) in TNFi-treated patients vs 0.39 (Sweden) and 0.28 (Denmark) in unexposed patients, and an age-sex-calendar-period-adjusted HR (95% CI) of 0.97 (0.72 to 1.33) (Sweden) and 1.45 (0.74 to 2.81) (Denmark) in TNFi exposed compared with non-exposed patients. For a total of 64 065 AS/PsA patients, the corresponding numbers were: 196 and 32 events, crude incidence rates of 0.59 and 0.87 in TNFi-treated patients vs 0.40 and 0.19 in unexposed patients, and HRs of 1.50 (1.07 to 2.11) and 3.41 (1.30 to 8.96), for Sweden and Denmark, respectively. For multiple sclerosis, the patterns of HRs were similar. Conclusions: Use of TNFi in AS/PsA, but not in RA, was associated with increased risk of incident neuroinflammatory disease, though the absolute risk was below one in 1000 patients/year.